Estimating Tertiary EFL Studentsâ€™ Enjoyment During Online Language Classes - Rosmen Rosmen (STKIP Yapis Dompu, 2023)
This study purposively conducted to investigate the EFL studentsâ€™ feeling during online learning in the pandemic situation and confirm their assumption on their teachersâ€™ approach providing the online classes. A survey to the seventy-seven students of STKIP Al Maksum Langkat was conducted. The psychometrically validated short form consists of nine positively-phrased items proposed by Resnik & Dewaele (2021) were distributed via Google Form which were classified in to three categories: â€˜personal enjoymentâ€™ (e.g., â€œIn my online or â€˜in-personâ€™ English class, I feel proud of my accomplishmentsâ€), â€˜social enjoymentâ€™ (e.g., â€œWe laugh a lotâ€ in the online class) and â€˜teacher appreciationâ€™ (to what extent the teacher is perceived as encouraging, friendly and supportive). The result asserted that students mostly strongly agree that there was no boredom in their online learning due to their understanding about school-closure because of the pandemic. Further, online learning environment affecting studentsâ€™ low participation so that their collaboration in the online classes straitened their feeling. Nevertheless, the perspectives of the teachers on the situation as well as their understanding of the advantages of online appliances have an effect on the enjoyment of the students.